The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jace.17419
|View full text |Cite
|
Sign up to set email alerts
|

Development of gypsum‐based composites with tensile strain‐hardening characteristics

Abstract: Brittle nature of gypsum restrains its wide application in construction industry. For improvement, a novel type of composite material, gypsum-based engineered cementitious composites (GS-ECC), was developed using specially chosen polyethylene (PE) fibers. This study investigated the rheological and mechanical properties of GS-ECC, that is, workability, uniaxial tensile and compressive behavior, flexural strength, etc The investigation showed that GS-ECC possessed excellent tensile strain-hardening behavior and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Water and water reducing agent were added for wet mixing for 5 min. When the slurry flowed uniformly, fibers were slowly added and stirred for about 10 min until uniform a dispersion was achieved [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The mixture was poured into a mold, vibrated, and cured at room temperature for 36 h. Finally, the mixture was cured in standard curing room for 28 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water and water reducing agent were added for wet mixing for 5 min. When the slurry flowed uniformly, fibers were slowly added and stirred for about 10 min until uniform a dispersion was achieved [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The mixture was poured into a mold, vibrated, and cured at room temperature for 36 h. Finally, the mixture was cured in standard curing room for 28 days.…”
Section: Methodsmentioning
confidence: 99%
“…Second, the cost of cementitious materials in ECC decreases by reducing the amount of cement and using some environmentally friendly cementitious materials, such as fly ash. This method has been widely used [ 11 , 15 , 16 , 17 ]. Wang et al [ 11 ] improved the strength of cementitious material by adding calcium sulfate, and the content of fly ash accounted for 60% of the cementitious material.…”
Section: Introductionmentioning
confidence: 99%
“…Viscosity-modifying agent (VMA) based on cellulose ethers, such as hydroxyethylmethyl cellulose (HEC) or hydroxypropylmethyl cellulose (HPMC), is commonly used to improve the workability and stability of the fresh concrete mixture. In terms of ECC, VMA as an admixture was added to adjust the rheological properties of the fresh matrices for achieving a uniform dispersion of fibers in previous studies (Wang et al, 2020a;Wang et al, 2020b) considering that CNF also can impact the rheological performance of the fresh paste, and it is reported that CNF results in the enhancement of the microstructure and mechanical properties of cement-based materials (Ghahari et al, 2020;Hisseine et al, 2020). In this study, CNF, regarded as an alternative to common VMA, was used to develop and reinforce ECC.…”
Section: Introductionmentioning
confidence: 99%